Characterization and phylogenetic analysis of the complete chloroplast genome sequence of Dendrobium hainanense (Orchidaceae) - Lei Zhao; Peizhang Chen; Wenchang Li; Zhe Zhang (Mitochondrial DNA. Part B. Resources, 2024)
In this study, we report the chloroplast (cp) genome of Dendrobium hainanense. The cp genome was 151,367 bp in length; the overall CG content of the genome was 37.46%. The length of the large single-copy (LSC) region was 83,938 bp, and 15,829 bp in a small single-copy (SSC) region, and a pair of inverted repeats (IRs) of 12,900 bp. One hundred and twenty-seven genes were predicted, including 81 protein-coding genes, 38 genes for tRNA, and eight genes for rRNA. The results of phylogenetic tree showed that Dendrobium hainanense had the closest genetic relationship with Dendrobium parciflorum. This study will be help to understand the genetic diversity of Dendrobium.